Advanced Electrode Materials - Ashutosh Tiwari, Filiz Kuralay, Lokman Uzun (Advanced materials series, 2016)
This book covers the recent advances in electrode materials and their novel applications at the cross-section of advanced materials. The book is divided into two sections: State-of-the-art electrode materials; and engineering of applied electrode materials. The chapters deal with electrocatalysis for energy conversion in view of bionanotechnology; surfactant-free materials and polyoxometalates through the concepts of biosensors to renewable energy applications; mesoporous carbon, diamond, conducting polymers and tungsten oxide/conducting polymer-based electrodes and hybrid systems. Numerous approaches are reviewed for lithium batteries, fuel cells, the design and construction of anode for microbial fuel cells including phosphate polyanion electrodes, electrocatalytic materials, fuel cell reactions, conducting polymer based hybrid nanocomposites and advanced nanomaterials.